Tolerogenic antigen-specific vaccine induces VISTA-enriched regulatory T cells and protects against arthritis in DRB1∗04:01 mice - Romero-Castillo, Laura; Pandey, Rajan Kumar; Xu, Bingze; Beusch, Christian M.; Oliveira-Coelho, Ana; Zeqiraj, Kejsi; Svensson, Carolin; Xu, Zhongwei; Luo, Huqiao; Sareila, Outi; Sabatier, Pierre; Ge, Changrong; et al. (Elsevier BV, 2025)
Rheumatoid arthritis (RA) is a chronic autoimmune disease characterized by joint inflammation, cartilage damage, and bone erosion. Despite improvements with the introduction of biological disease-modifying anti-rheumatic drugs (DMARDs), RA remains an incurable life-long disease. Advancements in peptide-based vaccination may open new avenues for treating autoimmune diseases, including RA, by inducing immune tolerance while maintaining normal immune function. We have already demonstrated the efficacy of a potent vaccine against RA, consisting of the mouse major histocompatibility complex class II (Aq) protein bound to the immunodominant type II collagen peptide COL2259-273, which needed to be galactosylated at position 264. To translate the vaccine to humans and to further enhance vaccine efficacy, we modified the glycine residue at position 265 and conjugated it with the human DRB1∗04:01 molecule. Remarkably, this modified vaccine (named DR4-AL179) provided robust effectiveness in suppressing arthritis in DRB1∗04:01-expressing mice without the need for galactosylation at position 264. DR4-AL179 vaccination induces tolerance involving multiple immunoregulatory pathways, including the activation of V-type immunoglobulin domain-containing suppressor of T cell activation (VISTA)-positive nonconventional regulatory T cells, which contribute to a potent suppressive response preventing arthritis development in mice. This modified RA vaccine offers a novel therapeutic potential for human autoimmune diseases.